Makna Simbolik Tari Ilau Nagari Sumani, Kabupaten Solok Sumatera Barat - Yesriva Nursyam; Supriando Supriando (PANGGUNG, 2018)
AbstractIlau dance is one type of dance in Minangkabau which is performed in traditional customs in Nagari Sumani. The tradition of the Nagari Sumani community in the wedding ceremony has its own uniqueness that is interesting to study. As a cultural product, ilau dance has meanings and symbols, which is manifested in a visual form that gives a certain meaningful content but is communicative for its people. This study aims to find the symbolic meanings of Ilau dance. This study uses a descriptive method with data collection through observation and interviews to get an overview of the subjects and research objects of the ilau dance. The results of the study show that the symbolic meaning of the Ilau dance can be interpreted from the people’s point of view and their understanding of cultural life, both textually and contextually.Keywords: Ilau dance, marriage custom, symbol, Nagari Sumani.AbstrakTari Ilau merupakan salah satu jenis tarian di Minangkabau yang dipertunjukkan dalam adat perkawinan di Nagari Sumani. Tradisi masyarakat Nagari Sumani dalam upacara perkawinan memiliki keunikan tersendiri yang menarik untuk dikaji. Sebagai sebuah produk budaya, tari ilau memiliki makna dan simbol, yang diwujudkan dalam bentuk visual yang memberi muatan makna tertentu, tetapi bersifat komunikatif bagi masyarakatnya.  Penelitian ini bertujuan untuk menjawab makna simbolik yang terdapat pada tari Ilau. Penelitian ini menggunakan metode deskriptif dengan perolehan data melalui observasi dan wawancara untuk mendapatkan gambaran terhadap subyek dan obyek penelitian tari ilau. Hasil penelitian menunjukkan bahwa makna simbolis tari Ilau dapat diinterpretasi dari sudut pandang dan pemahaman berkaitan dengan kehidupan masyarakat pemilik kebudayaan, baik secara tekstual maupun kontekstual. Kata kunci: Tari ilau, adat perkawinan, simbol, Nagari Sumani.